The recursive definition used to generate the sequence {3, 6, 3, 6, 3,...} is:
[tex]a_n = a_{n - 1} + 3(-1)^n[/tex] where [tex]a_1 = 3[/tex] and [tex]n\geq 2[/tex]
Solution:
Given sequence is 3, 6, 3, 6, 3,...
To find: recursive definition for the sequence
First term in the sequence is 3
Then you add on 3 to get to 6 as the second term
Then add -3 to get 3 as third term
This pattern goes on forever
3 + 3 = 6
6 - 3 = 3
3 + 3 = 6
6 - 3 = 3
and so on
So we can generate a recursive definition as:
Let [tex]a_n[/tex] be the nth term and "n" denotes the term's location
[tex]a_1[/tex] is the first term of sequence
[tex]a_n = a_{n - 1} + 3(-1)^n[/tex] , where [tex]a_1 = 3[/tex] and [tex]n\geq 2[/tex]
Here, [tex]3(-1)^n[/tex] is used to denote , we add on either +3 or -3 to the previous term to get next term